2021
DOI: 10.3389/fpsyt.2021.622366
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Lockdown: A Study on Italian Undergraduates During the COVID-19 Pandemic

Abstract: The current study aimed at increasing our understanding of the psychological impact of the COVID-19 lockdown on undergraduate students, particularly with respect to the association between personality traits; defense mechanisms (DMs); depression, anxiety, and stress symptoms (DASSs); and compliance with the government recommended health measures. A sample of 1,427 Italian undergraduate students were administered the Personality Inventory for the DSM-5—Brief Form; the Defense Style Questionnaire-40; and the Dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Overall, our study showed that self-reported measures of psychological distress were elevated relative to average scores for the general adult population. Participants reported higher levels of depression and stress during the COVID-19 lockdown, which is consistent with results from other studies during the same period [e.g., ( 88 91 )]. The sample reported higher scores on the SCL-27 compared with population norms, supporting recent studies that have indicated an increase in symptom scores measured by the SCL-27 during self-isolation ( 92 ).…”
Section: Discussionsupporting
confidence: 90%
“…Overall, our study showed that self-reported measures of psychological distress were elevated relative to average scores for the general adult population. Participants reported higher levels of depression and stress during the COVID-19 lockdown, which is consistent with results from other studies during the same period [e.g., ( 88 91 )]. The sample reported higher scores on the SCL-27 compared with population norms, supporting recent studies that have indicated an increase in symptom scores measured by the SCL-27 during self-isolation ( 92 ).…”
Section: Discussionsupporting
confidence: 90%
“…Studies on healthy adults' self-reports of personality collected during the pandemic did not gave a definite answer to this question: most of the studies found out that the scores collected during the pandemic with instruments such as the Brief HEXACO Inventory (46), the International Personality Item Pool's IPIP-NEO (47), the reduced Temperament and Character Inventory (48), the Personality Inventory for the DSM-5-Brief Form (49), or the various versions of the Big Five Inventory (50)(51)(52)(53) remained stable (i.e., remained within one standard deviation of the normative means) in comparison with those collected before it [e.g., (39,(54)(55)(56)(57)]. Other studies, however, found that scores changed beyond one standard deviation from the normative means [e.g., (58,59)], or found significant changes in the pre-vs. during pandemic comparisons of scores: for example, significant changes were observed, using the Big Five Inventory-2 questionnaire (53), in the neuroticism and extraversion traits of the big-5 model of personality in a sample of 2,137 U.S. citizens who were tested before (early February 2020) and during (second half of March 2020) the pandemic outbreak in the U.S. (60).…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of the COVID-19 outbreak, the literature has assessed the psychological impact derived from this pandemic. In this way, higher levels of emotional symptoms have been found in the general community, such as greater worries, stress, anxiety, depression, among others (Sandín et al, 2020;Biondi et al, 2021;. Moreover, higher levels of stress, anxiety, and depression were found in the healthcare workers (Dosil et al, 2020).…”
Section: Discussionmentioning
confidence: 88%